Unfair Contract Terms Act 1977: does it provide a good model in regulating risk allocation provisions in oilfield contracts in Malaysia? - Wan Zahari, Wan Mohd. Zulhafiz (Inderscience, 2015)
The unequal bargaining power of the parties in the oil and gas industry has lead to the imbalanced contractual risk allocation in oilfield contracts in Malaysia. In this regard, there is a prospect that the operators pass an unfair share of the risks on to the contractors. However, the contractors might still enter into such imbalanced agreement to secure a job and thereby assume these risks. In this paper, it is argued that a statutory controlling mechanism, such as Unfair Contract Terms Act 1977 (UCTA) in the UK, should be adopted to protect the liability of the contractor in relation to the risk allocation provisions of oilfield contracts in Malaysia. This paper seeks to analyse the deficiencies of the risk allocation provisions of oilfield contracts in Malaysia and to consider whether the principle of reasonableness test as provided in UCTA could provide a potential solution. It will employ a combination of case study and analysis.